Controle e resistência à doenças foliares em genótipos de milho, produtividade e qualidade sanitária de grãos cultivados na região Centro-Sul do estado do Tocantins - Chagas, Jaíza Francisca Ribeiro (Universidade Federal do Tocantins, 2017)
The demand for increasing maize productivity it makes it a constant search for better techniques in the management of plant nutrition and products that are effective in protecting plants against pathogens, directly improving the quantity and quality of grain. Every year comes by increasing the planting of corn in area and productivity in the Tocantins state, so that the studies conducted here aimed to provide information on the control of foliar diseases in corn genotypes, productivity and sanity quality beans grown in the southern state of Tocantins. In the first chapter it was evaluated nitrogen fertilization on foliar disease severity, productivity and biochemical responses in corn hybrids. The tested doses influenced the severity of disease evaluated. Higher productivity and thousand grain weight were obtained with higher doses of nitrogen. There was a correlation between catalase (CAT) and superoxide dimutase (SOD) enzymes, with progress curve Area Under Bipolaris leaf spot, demonstrating increased activity at doses where there was a greater disease severity. There was a lower concentration of the amino acid proline, where higher severity. The total amino acid content was higher where there was the use of the highest dose of N. In the second chapter, it was verified the effect of disease control and corn yield by applying phosphite and fungicide. The disease control was more effective with the application of fungicide isolated and with the mixture of the phosphite to the fungicide. Best yields were obtained where there was application of phosphite, both in mixture as isolated. The third chapter aimed to study the occurrence of diseases and maize genotypes grown in the state of Tocantins cerrado. The diseases observed in the experiments were spot Bipolaris, polissora rust, anthracnose leaf blight and stain Curvularia, and the bipolar stain had higher incidence and severity in all genotypes. Most cultivars demonstrated good production potential in both experiments. In the fourth chapter, we analyzed the health quality asymptomatic grain and rot of corn cultivars in the state of Tocantins. The fungal genus mostly found in rancid and asymptomatic grains was the Fusarium, and we found a high incidence in all evaluated grains.